Answer:
A
Step-by-step explanation:
Because you have to use the Pythagorean theorem to solve for this.
I think straight angles ?
b
Step-by-step explanation:
because it will be right always because if you mutiply all of them then you get your right answer
= <span><span>−x</span>+6</span>
<span>=<span><span> −<span>3x</span></span>+3</span></span>
<span>= </span><span><span>−x</span>+6</span>
= <span><span>2x</span>−3</span>
<span>= <span><span>−<span>4x</span></span>−<span>17</span></span></span>